Specific issues of vertical jumps as fundamental performance diagnostics tools - Richter, A.; Stein, T.; Woll, A.; Potthast , W.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Vertical jumping ability is an important factor in many sports. Therefore, the performance diagnostics with counter-movement jumps (CMJ) and drop jumps (DJ) became a fundamental tool to measure explosive leg power. Both jumps have been frequently assessed in various subject groups. However, most previous studies involved adult male participants, who were experienced in jumping, and data from younger subjects with less jumping experience is rare. Therefore, the focus at first was to set on the analysis of CMJ and DJ performance in children and adolescents of different age, gender and activity level in general. Furthermore, specific aspects of arm-swing in CMJ are investigated in good and poor jumpers to compare kinematic and kinetic parameters of selected joints, and inter-joint coordination of different joints between groups and CMJ with and without arm-swing.